Delivering Knock Your Socks Off Service, 5th Edition - ASSOCIATES, PERFORMANCE; Bush, John (AMACOM, 2011)
Who would've thought that a practical, fun, easy-to-read customer service book would capture the hearts of hundreds of thousands of readers? Now, celebrating its 20th anniversary, Delivering Knock Your Socks Off Service has been completely revised and is better than ever! Still the go-to guide on providing the kind of outstanding service that keeps customers coming back, the fifth edition combines powerful tools and techniques with real-world examples and all-new chapters on using social media for communication and service recovery, owning service encounters, responding positively to negative feedback, and more. The book provides readers with proven tips and strategies for: • Exceeding customer needs and expectations • Determining the right times to bend or break the rules • Becoming fantastic fixers and powerful problem-solvers • Using the RATER factors to wow your customers • Understanding cultural and generational differences • Becoming a listening post • Coping effectively with "customers from hell" With people surrounded by more choices and information than ever before, true customer loyalty has become increasingly difficult to attain. Combining timeless wisdom and up-to-the-minute methods, Delivering Knock Your Socks Off Service is the book no customer service professional can afford to be without.